The Social Responsibility of The Private Sector in Social Development in The Kurdistan Region - Iraq: Theoretical Analytical Study - Aram IbrahIm Hussen; Adnan fareeq shaheen (QALAAI ZANIST JOURNAL, 2022)
The study aimed to identify the role and concept of social responsibility of private sector institutions in social development and to identify the most important principles and dimensions on which they are based in society and the extent to which the Kurdistan private sector institutions adopt them and knowing their role in achieving social development. The study found a group of results the most important is the absence of legislative, legal and institutional frameworks that would enhance the concept of social responsibility for private sector institutions, which led to the lack of an integrated concept of social responsibility for private sector institutions, and also that the contribution of the private sector in providing donations, zakat and subsidies to society is not sufficient to judge it to bear responsibility. Social activities are strictly limited, i.e. the limited activities practiced by private sector institutions in the field of community service and their focus on specific areas.